2019
DOI: 10.1002/cjce.23374
|View full text |Cite
|
Sign up to set email alerts
|

Effort of ionic liquids with [HSO4] on oxidative desulphurization of coal

Abstract: Sulphur dioxide and soot produced during coal combustion are the main air pollution sources and increased emission of PM 2.5 (particle matter with an aerodynamic diameter less than or equal to 2.5 mm) in China. In this investigation, two imidazolium ionic liquids (ILs), namely, 1-butyl-3-methyl imidazolium bisulphate ([C 4 C 1 im][HSO 4 ]) and 1-carboxymethyl-3-methylimidazolium bisulphate([HOOCCH 2 mim][HSO 4 ]), were used to remove sulphur from coal combined with 30 % hydrogen peroxide (H 2 O 2 ) based on ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…have examined over the ability of oxidative desulphurization of coal, as the sulfur dioxide and soot which emerges out during the combustion of coal are the main sources of air pollution. In their investigation, they have used imidazolium based ILs, namely, 1-butyl-3-methylimidazolium bisulfate and 1-carboxymethyl-3methylimidazolium bisulfate to extract sulfur from coal [37] Patra et al analyzed the effect of nitro groups on desulfurization efficiency of benzyl substituted imidazolium-based ionic liquids. The liquid-liquid microextraction approach was adopted and the parameters influencing extraction efficiency, such as the effect of IL volume, concentration and rotation period, were extensively studied.…”
Section: Crude Oil Industrymentioning
confidence: 99%
“…have examined over the ability of oxidative desulphurization of coal, as the sulfur dioxide and soot which emerges out during the combustion of coal are the main sources of air pollution. In their investigation, they have used imidazolium based ILs, namely, 1-butyl-3-methylimidazolium bisulfate and 1-carboxymethyl-3methylimidazolium bisulfate to extract sulfur from coal [37] Patra et al analyzed the effect of nitro groups on desulfurization efficiency of benzyl substituted imidazolium-based ionic liquids. The liquid-liquid microextraction approach was adopted and the parameters influencing extraction efficiency, such as the effect of IL volume, concentration and rotation period, were extensively studied.…”
Section: Crude Oil Industrymentioning
confidence: 99%
“…[15,16] Ionic liquids are also used to investigate coal properties. [17,18] Li et al treated coals with ionic liquids of different concentrations to study the changes in pore characteristics and fractal dimension. [19] The results show that the total pore volume of coal samples treated with ionic liquid is larger than that of the coal sample treated with water.…”
Section: Introductionmentioning
confidence: 99%
“…They also found that the mixture of the [HOOCCH 2 mim][HSO 4 ]–30% H 2 O 2 solution can remove 16.76% of organic sulfur, and imidazolium ionic liquids are more efficient than the pyridinium ones. 26 …”
Section: Introductionmentioning
confidence: 99%